2008
DOI: 10.1080/00103620701880925
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Macro Cations Status impacted by Long‐Term Applied Poultry Litter

Abstract: Most ethnic populations worldwide consume poultry products. Whereas poultry litter (PL) is a traditionally inexpensive and effective fertilizer to improve soil quality and agricultural productivity, overapplication to soils has raised concerns because excess nutrients in runoff could accelerate the eutrophication of fresh bodies of water. A long-term field experiment of land application of PL to soils used for pasture growth has been maintained for nearly two decades in the Sand Mountain region of north Alabam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
12
1
Order By: Relevance
“…Various studies found that greater CEC is associated with greater soil organic matter (SOM) contents, due to a higher degree of oxidation of SOM and a higher surface area for cation adsorption sites (Liang et al, 2006;Sombroek et al, 1993). Electrical conductivity was slightly higher (P = 0.0752) in litterapplied soils compared to IF applications, which was consistent with previous long-term studies (He et al, 2008;Kingery et al, 1994). Poultry litter added to the soil mineralizes and release the nutrients and salts to the soil leading to an increase of soil EC and salt content.…”
Section: Soil Residue Fertilitysupporting
confidence: 79%
“…Various studies found that greater CEC is associated with greater soil organic matter (SOM) contents, due to a higher degree of oxidation of SOM and a higher surface area for cation adsorption sites (Liang et al, 2006;Sombroek et al, 1993). Electrical conductivity was slightly higher (P = 0.0752) in litterapplied soils compared to IF applications, which was consistent with previous long-term studies (He et al, 2008;Kingery et al, 1994). Poultry litter added to the soil mineralizes and release the nutrients and salts to the soil leading to an increase of soil EC and salt content.…”
Section: Soil Residue Fertilitysupporting
confidence: 79%
“…The objectives of this study were to evaluate the impact of PL application history (0, 5, 10, 15, and 20 years) on accumulation and distribution of total P, Mehlich 3 extracted P, total N, ammonium (NH 4 )-N, and nitrate (NO 3 )-N through soil profiles (0-60 cm). The impacts on trace elements and macro cations have been reported elsewhere (He et al 2008, Tazisong et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most of the 1.5 million Mg of broiler litter generated in Alabama during 1999 was used for fertilizing pastures (Kpomblekou et al 2002). But overapplication of PL to soil may lead to detrimental environmental effects, such as pollution of ground and surface waters due to leaching and runoff of nutrients and soil accumulation of heavy metals (Franzluebbers et al 2002, He et al 2008, Kingery et al 1994, Tazisong et al 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cattle feedlot litter increased soil organic carbon and water stable aggregates, and decreased bulk density and hydraulic conductivity of disturbed soils [18]. Application of poultry litter on pasture soils over a 20-yr period altered soil properties (pH, electric conductivity, and bulk density) macrocation levels (Ca, K, Mg and Na levels), and increased hay yields [19]. In this study, the authors also noted that the labile form of phosphorus increased following long-term sequential application of poultry litter.…”
Section: Introductionmentioning
confidence: 99%